Bill Readings and the supplement - Skordili, Beatrice (Surfaces, 1996)
"Bill Readings and the supplement" is an attempt to trace the various connections of Bill Readings' work on Milton with his ethics of reading and writing, his pedagogical stance in class and relationship to his students, and finally his relationship to the name. The paper imagines setting up the rudiments of a symptomatic grapho-biography that juxtaposes itself to psychoanalytic readings-with their attendant implications of mastery.